The Impact of Organic, Inorganic Fertilizers, and Biochar on Phytochemicals Content of Three Brassicaceae Vegetables - George Fouad Antonious (Applied Sciences, 2023)
The need for soil fumigants of natural origin such as glucosinolates (GSLs) has increased due to the general prevention of manmade soil fumigants. GSLs and other phytochemicals (vitamin C and phenols) present in Brassica vegetables such as turnips, arugula, and mustard have antioxidant properties, and hence have important health attributes. The study examined how different soil amendments (chicken manure CM, vermicompost Vermi, horse manure HM, sewage sludge SS, elemental inorganic fertilizer Inorg, organic fertilizer Org, and biochar) impact the concentrations of glucosinolates (GSLs), vitamin C, phenols, and reducing sugars in three varieties of turnips (Purple Top White Globe PTWG, Scarlet Queen Red SQR, and Tokyo Cross TC), arugula, and mustard greens grown under field conditions. The results showed that mustard greens contained higher concentrations of GSLs (974 µg g−1 fresh shoots) than arugula (651 µg g−1 fresh shoots), and the TC variety of turnip had the highest concentrations of GSLs, vitamin C, and sugars. Additionally, amending the soil with SS, CM, and HM significantly increased the vitamin C content in mustard shoots by 82%, 90%, and 31%, respectively, and the total phenols by 77%, 70%, and 36%, respectively, compared to the control treatment. The increased inorganic fertilizers cost, and availability of large amounts of animal manure made animal manure application to cropland an attractive disposal option.